Precambrian Turbidites of Eqe Bay, Baffin Island: Stratigraphic, Structural and Geochronological Constraints on the Evolution of Canada's Arctic Greenstone Belts - Folkesson, Carl-Philippe; Saumur, Benoit M.; Davies, Joshua; Hey, Jon; Johnston, Stephen T (Geological Survey of Canada, 2023)
The Archean greenstone belts of the Mary River Group (2865-2706 Ma), or MRG, occur in northern Baffin Island and remain poorly understood in terms of structure, stratigraphy and metallogeny. The Eqe Bay greenstone belt is the least deformed and metamorphosed exposure of the MRG, and is divisible into a stratigraphically lower metavolcanic sequence and an overlying metasedimentary sequence. The upper sequence of the Eqe Bay belt consists mainly of a large turbiditic formation that unconformably overlies the lower volcanic and volcaniclastic sequence. Two primary units make up the metasedimentary sequence: (U1) a jointed polygenic conglomerate with a variable thickness between 100 and 250 m, that stratigraphically overlies the lower volcanic domain along the main unconformity; and (U2) an turbiditic formation with a maximum thickness of 6.5 km consisting mainly of wackes and graywackes including siltstone, argillites and meter-scale beds of granular polygenic conglomerate interbedded with sandstone. Two subunits are recognized within the turbidite succession: (U2.1) a distinctive 5 to 10m thick quartzite layer located near the base of the U2 turbidite sequence layer located near the base of the U2 turbidite sequence; and (U2.2) a thin iron formation interbedded with phyllite and garnet-rich schist. The unconformity at the base of the metasedimentary sequence is coincident with a major NE-SW trending, mylonitic shear zone that extends along the length of the Eqe Bay belt. We distinguish three deformation events affecting the metasedimentary belt: the first deformation is represented by a penetrative bedding-parallel foliation (S1) that is assumed to have developed during isoclinal folding. The second (S2) records is a penetrative fabric oblique to S1 associated with local F2 folds. The third event is recorded in localized strongly deformed zones that are characterized by a shallowly dipping crenulation cleavage (S3). U-Pb geochronological work on magmatic and detrital zircons provides an update on the stratigraphy ...